Phosphorus recovery from domestic sewage sludge in the presence of waste grape pruning biochar - M. Piri; E. Sepehr (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Phosphorus is an essential and limiting nutrient for all living organisms. Although phosphorus is a finite resource on earth, it is usually wasted today. Precipitation of struvite from waste residues is mainly carried out to recover phosphorus. This study aimed to investigate the percentage of phosphorous recovery from sewage sludge in the presence of grape-biochar via the formation of biochar/struvite precipitates. METHODS: Different amounts of grape-biochar were applied to recover nutrients (phosphorus, nitrogen, and magnesium) from sewage sludge via the formation of struvite by digestion of sewage sludge with H2SO4 and the molar ratio of magnesium/ ammonium/ phosphorus in 2:1:1 at pH=8.5. Solubility and release properties of the precipitates were determined and the equations, such as first-order, parabolic diffusion, power function, and simple Elovich models, were fitted to the kinetic data.FINDINGS: The phosphorus recovery from sewage sludge increased by application of grape biochar in the precipitation system, and the accumulation release of nutrients (phosphorus, nitrogen, and magnesium) from samples increased in the presence of grape biochar, especially in high amounts. Increasing the remove and recovery of phosphorus from sewage sludge by application of grape-biochar decreased the incidence of eutrophication, as an environmental dilemma, and provided the requirement for phosphorus-fertilizers by solid waste management. The solubility of the samples was 0.5 mole per liter hydrochloric acid > in 20 gram per liter citric acid > water. The results showed that the phosphorus - cumulative - release of composites in water good fitted the parabolic kinetic model (R2=0.97-0.99), whereas it followed the simple Elovich model (R2=0.86-0.92) in 0.5 mole per liter hydrochloric acid and first-order kinetics model (R2=0.76-0.92) in 20 gram per liter critic acid.CONCLUSION: The results indicated that the presence of grape-biochar for recovery of phosphorus from sludge as struvite had a good potential for increasing the release of nutrients for the formation of struvite, and these precipitates had a high potential to be used as a slow-release phosphorus-fertilizer.